Domination and disintegration: Adorno and critical social theory. - Foster, Roger Stephen. (University of Ottawa (Canada), 2000)
The central claim of my thesis is that Theodor Adorno's social theory harbours important insights which can bring to light significant deficiencies and weaknesses in the works of contemporary critical theorists. In order to substantiate this claim, I argue that Adorno's philosophical and sociological writings embody a coherent and systematic version of critical social theory. I then attempt to place Adorno's version of critical social theory in critical and constructive dialogue with the successors to the tradition of Frankfurt School critical theory (Jurgen Habermas and Axel Honneth). This is achieved by reconstructing and reinterpreting Adorno's key theses through insights developed in contemporary social theory. Part One demonstrates, firstly, how Adorno's critical social theory developed from out of the problems of the earlier social-theoretic 'paradigms'. In chapter two, I argue that Adorno, in Negative Dialectics, develops a conception of critical theory as a 'critical dialectic of concepts', derived from a synthesis of the Durkheimian sociology of knowledge, and Hegelian dialectic. Chapter three attempts to substantiate and develop this thesis, and also shows how Adorno develops a theory of linguistic reification. In chapter four, I attempt to expound the social theory underlying the philosophical arguments of Negative Dialectics. In Part Two, I deploy the insights derived from the analysis of Adorno's work in order to furnish a critique of Habermas's critical theory, concerned with its failure to develop an adequate critique of class- and group-specific domination (chapter five) and problems stemming from its formal/abstract conception of moral-practical reason (chapter six). I then turn, in Part Three, to the critical theory of recognition. It is argued that, by returning the concept of social struggle to the centre of the analysis, the theory of recognition is able to theorize structures of domination and oppositional praxis far more adequately than the Habermasian account. However, I argue that this theory needs to integrate insights deriving from Adorno's thesis of integration through domination. I argue that the concept of symbolic power provides for a plausible reconstruction of Adorno's integration thesis, by interpreting integration through domination as occurring at the symbolic rather than the psychic level. In the final chapter, I draw upon contemporary social theory in order to furnish an interpretation of Adorno's social theory as articulating a twofold distortion of instrumental reason, which I characterize as a dialectic of increasing integration through domination, and intensifying lifeworld disintegration.
Keywords: Philosophy.